Validation of End Effector Matrix for Robotic Kit OWI-535 using Matlab and Robo Analyzer - Bhivraj Suthar; Tanmay Shrivastava; Lamyanba Heisnam (IAES International Journal of Robotics and Automation (IJRA), 2016)
This paper presents the validation of the end effector matrix having D-H parameter of the 4 DOF educational manipulator OWI-535 by MAT-LAB and Robo Analyzer. Transformation matrix of order 4x4 which describes end effecter’s position and orientation with respect to the base reference frame. MAT-LAB programming which gives details about the translation steps of the manipulator simultaneously. Forward kinematics of OWI 535 robotic kit has been calculated by Mat-lab as well as Robo Analyzer. We had calculated the End effector matrix in both software and compare it. We found that the results are similar up to three digit in some elements and up to two digits from decimal in few elements and it was different after three digit from the decimal in end effector matrix.